PEMBARUAN PENDIDIKAN ISLAM NAHDLATUL ULAMA - Mahrus As’ad (Postgraduate State Islamic Institute (IAIN) Metro, 2014)
This article tries to understand and explain the basic concept and the essence of the NU educational reform (tajdīd) and the relationship of its schoolship view and its contribution to the Islamic educational resurgence after the Indonesia independence in meeting the new demands and the challenges of the modern era. Using the socio-historical-phenomenological approach, the result concludes that the basic concept of the NU educational reform is identical with the dinamization in the sense of change toward the correction and perfection of the condition of the Islamic education which is unbeneficial for its future. The essence of the effort is more focused on the substantial aspects of education than the technical-pedagogical ones in charge of the reposition and reactualization or revitalization of the social function of the Islamic education of the modern era. By reposition means the effort to redetermine the position of system and institution of traditional Islamic education, especially pesantren and madrasa, in order that they are suitable for new demands of modern education through the rehabilation of their old and absolete elements, and inovation by means of entering new and useful elements in to enpower their social functions optimally. Reactualization or revitalization means the effort to reactivate the basic principles of the classical Islamic education which are almost forgotten, on which the modern Islamic education hold them as the philosophical guidances for the universality of their values. Such effort are inseparable from the ideas and activities of the existence of the independence and progressive pesantren teachers (ulama) so that the conservativness of the schoolship views of the NU do not hinder and even motivate it to modernization. Its approach which enpowering the traditon legacies, and being integrally combined with the new elements of modern education distinguishes clearly theconcept of NU educational reform from the similar effort of the Muslim reformists which rest too much on the new elements of modern education. The new model of the system and institution of NU education has given valuable contributions not only to the completion and enrichment of the national education system and institution but also the strengthening the pillars of tenacity of the national culture as a whole.